Steinbeck in Vietnam - unknown:::Creator::::::::::::
John Steinbeck stands with two uniformed men in the Vietnam Highlands. Stending next to Steinbeck is his guide, Sam Gipson, Jr. In the background is a dirt clearing, more uniformed men, a field, trees, and mountains. The caption on the back reads: ...Next to John, his guide, Sam Gipson, Jr.